GAMBARAN POLA KONSUMSI PANGAN PADA MASA PANEN DAN MASA TANAM SERTA STATUS GIZI PADA ANAK BALITA DI DUSUN LAU GUNUNG KECAMATAN TANAH PINEM KABUPATEN DAIRI TAHUN 2012 - Jenni Wati Ginting; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The pattern of food consumption is a factor that has a direct impact to the nutritional status of under five children. The purpose of this research is to know the description the food comsumption pattern during the harvest and the planting seasons and nutritional status of under five children in the Lau Gunung. This research is descriptive with cross secsional design. Taking the sampel by total sampling of 64 under five children. The results of the research showed in the planting season that energy intake was categorized good 48.4%, moderate 28.1%, low 18.8%, deficit 4,7% and when during harvest time energy intake was good categorized 68.8%, moderate 25.0%, less 6.3%. Meanwhile, intake of proteins when post harvest good category 32.8, moderate, 40.6%, less 20.3%, deficit 6.3% and when during harvest time good category 78.1%, moderate 18.8% and less 3,1%. Nutritional status for the under five children in the planting and during harvest seasons accoding by index weight for age is 78.1% and 85.9%, accoding by index height for age is 84,4% and 84,4% and accoding by index weight for height is 73.4% and 87.5%, mostly in normal category. The recommended that to the housewife noticed provision in accordance with the pattern of food menu balanced diet and to the local healthcare providers to more focus for counseling on nutrition balanced the mothers with the under five children to improving the pattern of food consumption and nutrional status of under five children. Keywords: Alpha food pattern consumption, nutritional status, under five children, the planting, harvest